Antifungal, Insecticidal, and Repellent Activities of Rosmarinus officinalis Essential Oil and Molecular Docking of Its Constituents against Acetylcholinesterase and β-Tubulin - Ghizlane Houzi; Youness El abdali; Ghada Beniaich; Mohamed Chebaibi; Mohamed Taibi; Amine Elbouzidi; Samiha Kaioua; Abdeslam Asehraou; Mohamed Addi; Khalid Chaabane; Rachid Flouchi; Aimad Allali; et al. (Scientifica)
The aim of this study was to determine the phytochemical composition and evaluate the antifungal and insecticidal properties of Rosmarinus officinalis essential oil (EO). GC-MS was employed to analyze the phytochemical profile of the EO. The antifungal activity of the EO was assessed by calculating growth inhibition rates for Alternaria alternata, Fusarium oxysporum, and Botrytis cinerea. Repellent capacity and toxicity were evaluated through inhalation and contact tests on Callosobruchus maculatus. Molecular docking techniques were utilized to test the insecticidal and antifungal activities of rosemary EO. The analysis revealed a total of sixteen components in R. officinalis EO, with 1,8-cineole (40.80%) being the major constituent, followed by α-pinene (26.18%) and camphor (19.53%). Antifungal evaluation demonstrated a significant inhibitory impact on the mycelial growth of the tested fungi, with complete inhibition observed against B. cinerea. In terms of insecticidal capacity, the EO induced complete mortality of C. maculatus adults at a concentration of 1 μL/L air, with an inhalation test LC50 value of 0.62 μL/L air. Concentration-dependent reductions were observed in the number of both laid eggs and emerged insects, reaching a 99.36% reduction. The EO also exhibited a moderate effectiveness in repelling insects, with an average repellency rate of 50.83%. In silico analysis identified borneol as the most active molecule against insect acetylcholinesterase (PDB: 6ARY) with a Glide score of −7.254 kcal/mol. α-Caryophyllene showed the highest activity against B. cinerea β-tubulin (PDB: 3N2G) with a Glide score of −7.025 kcal/mol. These findings suggest that the EO derived from Moroccan Rosmarinus officinalis has potential as an effective natural agent against pathogenic fungi and could serve as a sustainable and environmentally friendly alternative as a bioinsecticide.